Canadian Occupational Performance Measure and Early Intervention: A Scoping Review. Issue 4 (1st October 2020) - Mathews, Skye B.; Mozolic-Staunton, Beth; Jefford, Elaine; Salehi, Nasim
ABSTRACT: This scoping review was prompted by the introduction of the National Disability Insurance Scheme (NDIS) in Australia, with a focus on young children with disabilities. The review began by investigating individualized outcomes measures used within Early Intervention (EI). The Canadian Occupational Performance Measure (COPM) was chosen as it is a widely used goal identification and outcome measurement tool. This paper explores how the COPM is used with young children with disabilities alongside other developmental assessments, what it contributes to the goal identification and outcome measurement process and the formulation of possible recommendations for early intervention (EI) services and the NDIS. This review highlighted that the COPM is currently used across several countries, with children aged birth-seven years with a range of disabilities. The COPM is being utilized to support the identification of functional goals and accurately track parent's satisfaction and their perception of their child's performance. This review indicated that the COPM builds in key elements of family-centered practice and would be a valuable tool to trial in the NDIS and to implement more broadly in early intervention internationally.